Relación del tiempo de protrombina como prueba de tamizaje de deficiencia adquirida del factor V de la coagulación y pronostica de muerte, en enfermedades con síntesis o consumo alterado de factores de coagulación - Octavio Martinez Betancur (Revista de la Facultad de Medicina, 1997)
Early determination of plasmic level of coagulation Factor V,is not predictive of mortality in clinical situations that disturb its hepatic synthesis or in diseases in which coagulation is activated through inflamatory pathway with intravascular consumption of coagulation proteins. Otherwise, prothrombin time ratio (PTR) is an indicator of outcome, independently of the primary illness. Apatient with a PTR higher than 1041 has 3.3 options of death more than a patient with a PTR or 1.0. The PTR is equally usefull as screening test for detection of low plasma levels of coagulation factor V.The best cutoff point of PTR for detection of factor V plasma level below 0.40 is 1.2, with 100% sensitivity and 45% specificity.